Relationship of Information Media and The Role of Parents on Genital Hygiene of Students - Indriyani Makmun; Rizkia Amilia; Siswi Utami (Midwifery and Nursing Research, 2022)
Background: Behavior that is lacking in hygiene care is being lazy to change pads when it causes bacteria to grow on the pads, the presence of vaginal discharge that causes discomfort in the female area. Good self-care during menstruation such as the use of proper sanitary napkins is that the pads should not be worn for more than six hours or the pads should be changed as often as possible when they are full of menstrual blood. Poor personal hygiene, especially in the genital area, is also a predisposing factor for cervical cancer (Muin et al, 2017) Methods: This study used an analytic study with a cross sectional approach in which the variables of information media, the role of parents and genital hygiene were studied at the same time. The research was carried out on August 5 – September 10 2020. The population in this study were students of SMA Negeri 1 Samarinda Class XII, which were 220 people. The sample in this study were 80 respondents. The sampling technique was random sampling. Analysis of the data used is the chi square test. Results: Based on the statistical test, a p-value of 0.004 was obtained, thus statistically there was a relationship between the information media and the personal hygiene and Based on statistical tests obtained p-value 0.000 thus statistically there is a relationship between the role of parents on the personal hygiene of SMA Negeri 1 Samarinda students.students. Conclusion: There is an influence of information media and the role of parents on genital hygiene in SMA Negeri 1 Samarinda students.